The Implementation of Constructive Approach to Improve Students' Problem Solving Ability and Self Concept Ability - Ruchiyat, Radifan Irsaly; Putra, Harry Dwi; Hendriana, Heris ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
The ability to solve mathematical problems is very important because it is one of the abilities that belong to the ability to think at a high level, therefore it must be trained. One of the factors that can support this is self-concept in doing something and especially in learning mathematics, but this is inversely proportional to the field which stated that self-concept and mathematical problem-solving abilities were still relatively low, the panelists were interested in conducting a research entitled the application of a constructivist approach to improve mathematical problem-solving abilities and self-concept of junior high school students, this study used the experimental method using experimental design and schematized by researchers therefore the researcher chose Krida Utama Middle School Jl. Gedong Lima No. V, Kertamulya, Kec. Padalarang, of course, with class divisions, namely an experimental class and a control class of 30 students. To measure mathematical problem-solving abilities and self-concept towards mathematics, the researcher makes a design or learning that is by the approach and makes measurement tools clear and accurate to see the results of constructivism learning, in the final posttest results from the experimental class obtains a Ngain value of 0.5968 in the learning category the experimental class has a pretty good category, and from the results of distributing the Self Concept questionnaire to learning mathematics using the constructivism approach it gets a percentage score of 77.71%, this indicates that learning using the constructivism approach can have a good effect on students' mathematical problem-solving abilities and concepts students towards learning mathematics.